A Flexible Film Bulk Acoustic Resonator Based on β-Phase Polyvinylidene Fluoride Polymer - Ting Wu; Hao Jin; Shurong Dong; Weipeng Xuan; Hongsheng Xu; Leihe Lu; Zijing Fang; Shuyi Huang; Xiang Tao; Lin Shi; Shuting Liu; Jikui Luo (Sensors, 2020)
This paper reports a novel flexible film bulk acoustic resonator (FBAR) based on <semantics> β </semantics> -phase polyvinylidene fluoride (PVDF) piezoelectric polymer. The proposed device was simulated and evaluated; then, a low-temperature photolithography process with a double exposure method was developed to pattern the electrodes for the device, which enabled the device to retain the piezoelectric properties of the <semantics> β </semantics> -phase PVDF film. Results showed that the β-phase PVDF FBARs had a resonant frequency round 9.212 <semantics> MHz </semantics> with a high electromechanical coupling coefficient ( <semantics> k 2 </semantics> ) of 12.76% ± 0.56%. The device performed well over a wide bending-strain range up to 2400 <semantics> μ ε </semantics> owing to its excellent flexibility. It showed good stability as a strain sensor with a sensitivity of 80 <semantics> Hz / μ ε </semantics> , and no visible deterioration was observed after cyclic bending tests. The PVDF FBAR also exhibited an exceptionally large temperature coefficient of frequency (TCF) of −4630 <semantics> ppm / K </semantics> , two orders of magnitude larger than those of other FBARs based on common inorganic piezoelectric materials, extraordinarily high sensitivity for temperature sensing. All results showed that <semantics> β </semantics> -phase PVDF FBARs have the potential to expand the application scope for future flexible electronics.